Light, heat and shadows: women's reflections on peacebuilding in post-conflict Bougainville. (3rd May 2016) - George, Nicole
Abstract: In this paper, I examine women's reflections on their experiences as peacebuilders during Bougainville's long years of conflict and the later period of conflict transition. I discuss the varying ways in which women, in this predominantly matrilineal society, recounted their contributions to conflict resolution as part of broader efforts to build peace. My interlocutors told stories of the distinctiveness of women's peace leadership, interwoven with references to global policy frameworks such as United Nations Security Council Resolution 1325. This appears, at first glance, to evidence a positive story of global and local influences coming together to produce positive peacebuilding outcomes charged by 'light and heat', as theorised by Annika Björkdahl and Kristine Höglund. I show this story to also be one of shadows, however, arguing that deeper scrutiny of these perspectives on women's peace leadership suggest they also mask difficult and more complex local realities.